2020
DOI: 10.3390/met10111491
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Mechanical Properties of a β-type Ti-Nb-Zr-Fe-O Alloy

Abstract: The influence of complex thermo-mechanical processing (TMP) on the mechanical properties of a Ti-Nb-Zr-Fe-O bio-alloy was investigated in this study. The proposed TMP program involves a schema featuring a series of severe plastic deformation (SPD) and solution treatment (STs). The purpose of this study was to find the proper parameter combination for the applied TMP and thus enhance the mechanical strength and diminish the Young’s modulus. The proposed chemical composition of the studied β-type Ti-alloy was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
(119 reference statements)
1
13
0
Order By: Relevance
“…An evaluation of osseointegration using similar bone morphometrical parameters as in this study has been previously performed [ 49 ]. These results support those of material development of Ti alloys to which Zr, Nb, and Ta have been added [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…An evaluation of osseointegration using similar bone morphometrical parameters as in this study has been previously performed [ 49 ]. These results support those of material development of Ti alloys to which Zr, Nb, and Ta have been added [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Resultssupporting
confidence: 84%
“… New bone formation rate ( a ), bone contact rate ( b ), and new bone thickness ( c ) for Ti–Ni, Ti–15–3–3, Ti–6–4 [ 16 ], and Ti–15–4–4 [ 16 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Ti-15Mo alloy was subjected to two techniques of intensive plastic deformation-high-pressure torsion and rotary swaging at room temperature-leading to the formation of an ultrafine-grained microstructure. It was found that, after isothermal ageing in both deformed conditions, precipitations of the α phase remain small and equiaxed even after ageing at 500 • C for 16 h. The other β alloy-Ti-Nb-Zr-Fe-O-was investigated by Cojocaru et al [7]. The influence of complex thermo-mechanical processing on its mechanical properties was analyzed.…”
Section: Development Of Microstructure and Operational Propertiesmentioning
confidence: 99%
“…The aim of the current study is directed at improving the physicochemical and mechanical properties as well as biocompatibility of Ti-based systems through crystal structure evolution (α → β) and new microstructure formation (micro → nano or ultrafine) via its chemical composition modification and processing method, respectively [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. β-type titanium alloys are interesting biomaterials for innovative implantable medical devices.…”
Section: Introductionmentioning
confidence: 99%